Exploring Students' Perspectives on Well-Being and the Change of United States Medical Licensing Examination Step 1 to Pass/Fail. Issue 4 (8th August 2021) - Mott, Nicole M.; Kercheval, Jacquelyn B.; Daniel, Michelle
Abstract: Phenomenon: In February 2020, the Federation of State Medical Boards and National Board of Medical Examiners announced that Step 1 of the United States Medical Licensing Examination would transition from a three-digit numerical score to a pass/fail outcome. While several opinion pieces have been authored on the potential implications of this change, no study has formally assessed the student voice. The purpose of this study is to explore medical students' perspectives of a pass/fail Step 1, with an emphasis on how this transition will impact their well-being. Approach: We conducted virtual focus groups from May 2020–June 2020 with first- and second-year medical students from six institutions (n = 30). We analyzed focus group content following the inductive and iterative constructivist approach to produce a thematic analysis. Findings: Participants included females (50%), males (47%), and one non-binary student. The majority were Caucasian (57%), followed by Asian (27%), African American (10%), and Hispanic or Latino/a (7%). Overall, students were confused regarding the decision to transition Step 1 to a pass/fail outcome. They expressed anxiety over the uncertainty of how a pass/fail Step 1 may impact future residency applications and pressure to re-allocate time and resources to other academic pursuits that would make them competitive. Students explicitly stated skepticism or disbelief that a pass/fail Step 1 would improve their well-being. Insights: While the decision to make Step 1 pass/fail was in part intended to decrease stress associated with performance on a single high-stakes exam designed for licensing purposes, it has led to increased worries for students, and secondary, unanticipated consequences remain to be seen. In this new setting, it will be imperative to provide clarity regarding the metrics used to evaluate students and to incorporate their perspectives in future policy changes.